The Effects of Pre-Instructional Support on ODL Learners in a Blended Learning Environment on the Learning of Mathematics - Siti Farina Sheikh Mohamed; Ng , Richard; Kaur, Abtar (2008)
Open Distance Learners at Open University Malaysia (OUM) are generally mature working adults who have left school for a considerable number of years. They may not remember the basic foundations in mathematics that they have learnt in school. Furthermore, mathematics being generally perceived as a tough subject and quite unpopular makes studying it again difficult after so many years; and this can result in anxiety among most learners. This is apparent in the low GPA of students taking basic and introductory mathematics at OUM. With this in mind, a study was conducted to provide this OUM Online Distance Learners (ODL) initial support to better prepare them for further understanding of mathematics in their future course of study. A one-day workshop was conducted to provide pre-instructional support to selected OUM learners. The workshop which was attended by 22 students, focused on the following: basics of numbers, algebra, logarithms and exponents. A pre-test was administered at the beginning of the workshop, the contents were then taught and finally a post-test was administered towards the end of the workshop. Further, an analysis was carried out to assess the impact of pre-instructional support on the long-term enhancement of student knowledge, motivation and sustenance for the course. At the end of the semester, students’ results were analyzed and compared with results of those students who did not attend the workshop. In addition, comparison of results was also made between students who were under the workshop instructor (current tutor) and students under another tutor.